2018
DOI: 10.1371/journal.pone.0209600
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of a dubious gene cluster to melanin biosynthesis in the tomato fungal pathogen Cladosporium fulvum

Abstract: Pigments and phytotoxins are crucial for the survival and spread of plant pathogenic fungi. The genome of the tomato biotrophic fungal pathogen Cladosporium fulvum contains a predicted gene cluster (CfPKS1, CfPRF1, CfRDT1 and CfTSF1) that is syntenic with the characterized elsinochrome toxin gene cluster in the citrus pathogen Elsinoë fawcettii. However, a previous phylogenetic analysis suggested that CfPks1 might instead be involved in pigment production. Here, we report the characterization of the CfPKS1 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…Out of four polyketide synthase genes, BsPKS1 was most strongly induced in the presence of S. vermifera (Figs S4c, S5b; Tables S4, S5). While the role of BsPKS1 in DHN‐melanin biosynthesis requires confirmation (Griffiths et al ., ), our data indicated that the presence of S. vermifera induces melanisation in B. sorokiniana hyphae (Fig. d).…”
Section: Discussionsupporting
confidence: 65%
“…Out of four polyketide synthase genes, BsPKS1 was most strongly induced in the presence of S. vermifera (Figs S4c, S5b; Tables S4, S5). While the role of BsPKS1 in DHN‐melanin biosynthesis requires confirmation (Griffiths et al ., ), our data indicated that the presence of S. vermifera induces melanisation in B. sorokiniana hyphae (Fig. d).…”
Section: Discussionsupporting
confidence: 65%
“…Botrytis cinerea Fruits and ornamental flowers [28] Gray mold [28] Up to 30% to 40% loss of strawberries [29] Blumeria graminis Wheat and barley [28] Mildews of grasses [28] 18% potential and 13% de facto loss of grains under current disease control [30] Colletotrichum spp. Fruits and vegetables [28] Anthracnose spots and blights [28] Losses >80% in tropical, sub-tropical and Mediterranean regions [31] Cladosporium fulvum Tomato [32] Tomato leaf mold [32] Loss of 10-25% during regular years [33] Fusarium spp.…”
Section: Fungal Pathogen Crops Disease Crop Loss (%)mentioning
confidence: 99%
“…Melanin is produced by a broad variety of pathogenic microorganisms and its production may be stimulated in stress responses, including bacteria, fungi and helminths (Nosanchuk and Casadevall, ), but unlike the well‐characterized protective role of melanin, its roles in pathogenesis are not so clear (Howard and Valent, ; Griffiths et al ., ). Similarly, in V .…”
Section: Introductionmentioning
confidence: 97%
“…Melanin is produced by a broad variety of pathogenic microorganisms and its production may be stimulated in stress responses, including bacteria, fungi and helminths (Nosanchuk and Casadevall, 2003), but unlike the well-characterized protective role of melanin, its roles in pathogenesis are not so clear (Howard and Valent, 1996;Griffiths et al, 2018). Similarly, in V. dahliae melanin biosynthesis driven by sensor and MAPK cascades is correlated with pathogenicity in some studies (Tzima et al, 2010;Tian et al, 2014;Tian et al, 2016;Wang et al, 2016;Yu et al, 2019;Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%